Mothering in Medicine: Parenting Policies in Canadian Medical Education - Gradstein, Roetka (Atlantis, 2008)
In 2005, 59% of Canadian medical school students were female. The feminization of medicine has brought many changes to the field including the utilization and creation of policies in support of women who chose to become parents during their medical training. This paper explores the institutional atmosphere in support of student parents in medical school and residency training in Canada.